2009
DOI: 10.1590/s0100-29452009000300043
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de diferentes substratos na produção de mudas de mangabeira (Hancornia speciosa)

Abstract: A mangabeira (Hancornia speciosa Gomes) é uma espécie frutífera nativa do Cerrado, que devido às características dos seus frutos apresenta enorme potencial de aceitação pelo mercado consumidor, além de apresentar expressivo potencial produtivo. Objetivou-se avaliar o efeito de diferentes substratos na produção de mudas de mangabeira em sacos de polietileno e determinar o melhor substrato para a propagação da espécie. O trabalho foi conduzido em casa de vegetação na Universidade Estadual de Mato Grosso do Sul, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
2
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 3 publications
6
14
2
12
Order By: Relevance
“…It was verified the emergence at 22 days after sowing (DAS), corroborating with the results of SILVA et al (2009) that found at 20 DAS. In the black screen, the S8 and S9 substrates, with 40 and 50% of vermiculite in their compositions, that added to 10% of sand, totaled 50 and 60% of inert and porous material on the substrate (Table 1), verified the largest ESI (Table 5), as well as in the aluminized screen, the S9 and S12 substrates because these substrates had favorable physical structure to the seedlings emergence.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…It was verified the emergence at 22 days after sowing (DAS), corroborating with the results of SILVA et al (2009) that found at 20 DAS. In the black screen, the S8 and S9 substrates, with 40 and 50% of vermiculite in their compositions, that added to 10% of sand, totaled 50 and 60% of inert and porous material on the substrate (Table 1), verified the largest ESI (Table 5), as well as in the aluminized screen, the S9 and S12 substrates because these substrates had favorable physical structure to the seedlings emergence.…”
Section: Resultssupporting
confidence: 86%
“…It was noted greater developments of stem diameter when using mixtures with porous and inert materials, these results are similar to those found by CARVALHO FILHO et al (2003) in 'jatobazeiro' seedlings. These results at 112 DAS, even at 5.0 cm above the stem, are much higher than those found by SILVA et al (2009), who obtained for stem diameter 2.89 mm and SILVA et al (2011) 2.19 mm, because, on average, in this study was verified values of 3.89 mm (S8 in A1) and 3.88 mm (S13 in A2).…”
Section: Resultscontrasting
confidence: 65%
See 1 more Smart Citation
“…The higher number of DFE resulted in a smaller emergence rate index (ERI) promoted by the SB+CC substrate than by the substrates BP and CB+FC. Silva et al (2009b) associate higher ERI with luminosity and with good drainage capacity substrate, which facilitates its oxygenation. A good substrate, to favor germination and emergence, it must exhibit a degree of porosity that allows the hydration and aeration, because to germinate and emerge seeds needs water and oxygen for their metabolism (NOGUEIRA et al, 2003).…”
Section: Resultsmentioning
confidence: 97%
“…The use of cattle manure as a component of substrate for seedlings is also appropriate and yields good results, as observed in Acacia sp. (CUNHA et al, 2006), Enterolobium contortisiliquum (ARAÚJO; PAIVA SOBRINHO, 2011), Harconia speciosa (SILVA et al, 2009b), Eugenia dysenterica DC. (MOTA et al, 2016).…”
Section: Introductionmentioning
confidence: 99%